Desempenho econômico e financeiro de empresas no Brasil entre 1995 a 2010: uma análise setorial entre empresas de capital fechado e aberto - Casturino, Vandersézar (Universidade do Vale do Rio dos Sinos, 2013)
This study had as objective to analyze if the economic and financial performance of public companies with opened capital is equal to those which remain with closed capital in the sector they act in Brazil. For achieving the analysis it was applied the non-parametric hypothesis test from U de Mann Whitney. It has developed an applied research, with described, documentary and amount of approaches. The sample counted with 1.246 (a thousand two hundred and forty-six) medium and large companies, from opened and closed capital, listed in Best and Biggest Exam magazine, by Abril Editor, with the announcement of the economic and financial performance indicators have been done on the basis of 21 classified sectors. Among the released indicators were selected the economic (the growth in sales, profitability of the legal property and sales profitableness) and financial (general indebtedness, a long-term indebtedness, general liquidity and current liquidity), expressed in values indexes and percentages, that represent the connection or ratio from the economical and financial information of the accounts demonstrations of the studied companies, utilized in the data analysis process. Stand out that, most of results of hypothesis test applied to the sectors attain an amount of 61,73% that accept the null hypothesis (H0) indicating that the distribution of the financ ial performance indicator or economic on average is the same among the companies with closed capital and the ones with opened capital. So the expectation in occurring dif ferences between the performance of the companies by virtue of own capital formation , can be considered by pointed results. But 31,12% about these results indicate rejection to the null hypothesis, so, there is the alternative hypothesis (H1) with the affirmation that the distribution of the performance financial indicator or economic on average is different between the companies with closed capital in connection to the ones with opened capital. Because of this there are indicators that point out significant differences between the performance of the two groups of companies, evidencing different results on the sectors, and they still follow the most of results a trend in being better in one of the studied groups. Such results point out a tendency to show a better economic and financial performance to the companies with closed capital.
Keywords: Desempenho econômico; Desempenho financeiro; Capital aberto; Capital fechado; Economic performance; Financial performance; Opened capital; Closed capital; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis